2021
DOI: 10.1186/s13756-021-00932-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of orthopedic physicians’ self-reported compliance with surgical site infection prevention: results of the WACH-trial’s pilot survey on COM-B factors in a German university hospital

Abstract: Background Prevention of surgical site infections (SSIs), which due to their long-term consequences are especially critical in orthopedic surgery, entails compliance with over 20 individual measures. However, little is known about the psychosocial determinants of such compliance among orthopedic physicians, which impedes efforts to tailor implementation interventions to improve compliance. Thus, for this professional group, this pilot survey examined psychosocial determinants of self-reported c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 39 publications
2
32
0
1
Order By: Relevance
“…It is probable that the lack of monetary or similar incentives, lack of personalization of the questionnaire, and the relative length of the questionnaire [36] affected the response rate in the WACH-survey. Additionally, the response rate of 73% among surgical doctors in orthopedics in the WACH questionnaire pretest [37] was achieved in a university hospital clinic-a context in which individual health care workers may have a higher affinity for research, and in which there was extraordinary support for the survey by the clinic's medical director. However, while efforts should be made to increase response rates in future studies of self-overestimation of compliance, there is also a decreasing trend of response rates among surgical doctors [35], and the response rate in the present survey at least falls within one standard deviation of the average rate reported in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that the lack of monetary or similar incentives, lack of personalization of the questionnaire, and the relative length of the questionnaire [36] affected the response rate in the WACH-survey. Additionally, the response rate of 73% among surgical doctors in orthopedics in the WACH questionnaire pretest [37] was achieved in a university hospital clinic-a context in which individual health care workers may have a higher affinity for research, and in which there was extraordinary support for the survey by the clinic's medical director. However, while efforts should be made to increase response rates in future studies of self-overestimation of compliance, there is also a decreasing trend of response rates among surgical doctors [35], and the response rate in the present survey at least falls within one standard deviation of the average rate reported in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Also, overestimation of one’s own compliance may play a role as it may cause impairment of actual compliance. For instance, in a survey of the physicians in our study clinic, self-reported HH compliance from 72% (“after contact with patient surroundings”) to 97% (“after body fluid exposure”) was found [ 11 ]. Notably, in that survey surgeons rated their own overall SSI-preventive compliance (including hand hygiene) higher than anesthesiologists [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…von "0 %" bis "100 %" [40] Handlungsphasen [37][38][39] Haben Sie sich in der letzten Zeit vor und nach infektionsgefährdenden Tätigkeiten die Hände desinfiziert?…”
Section: Realistische Oder Unrealistische Einschätzungunclassified